Very short cycles of postconditioning have no protective effect against reperfusion injury. Experimental study in rats - Ricardo Kenithi Nakamura; Carlos Henrique Marques dos Santos; Luciana Nakao Odashiro Miiji; Mariana Sousa Arakaki; Cristiane Midori Maedo; Maurício Érnica Filho; Pedro Carvalho Cassino; Elenir Rose Jardim Cury Pontes (Brazilian Journal of Cardiovascular Surgery, 2014)
Introduction: Ischemic postconditioning has been recognized as effective in the prevention of reperfusion injury in situations of ischemia and reperfusion in various organs and tissues. However, it remains unclear what would be the best way to accomplish it, since studies show great variation in the method of their application. Objective: To assess the protective effect of ischemic postconditioning on ischemia and reperfusion in rats undergoing five alternating cycles of reperfusion and ischemia of 30 seconds each one. Methods: We studied 25 Wistar rats distributed in three groups: group A (10 rats), which underwent mesenteric ischemia (30 minutes) and reperfusion (60 minutes); Group B (10 rats), undergoing ischemia (30 minutes) and reperfusion (60 minutes), intercalated by postconditioning (5 alternating cycles of reperfusion and ischemia of 30 seconds each one); and group C - SHAM (5 rats), undergoing only laparotomy and manipulation of mesenteric artery. All animals underwent resection of an ileum segment for histological analysis. Results: The mean lesions degree according to Chiu et al. were: group A, 2.77, group B, 2.67 and group C, 0.12. There was no difference between groups A and B (P>0.05). Conclusion: Ischemic postconditioning was not able to minimize or prevent the intestinal tissue injury in rats undergoing ischemia and reperfusion process when used five cycles lasting 30 seconds each one.